Culturally Embedded Organizational Learning for Global Responsibility - Ariane Berthoin Antal; André Sobczak (Business & Society, 2014)
This article proposes a multilevel model of Global Responsibility as a culturally embedded organizational learning process. The model enables an analysis of the way culture influences how responsibilities are defined and distributed in a culture at a given point in time, and how organizations learn to address new responsibilities in new ways when the context changes. The model starts at the organizational level and zooms in on the individual level as well as outward to the local, national, and international levels. The case of a French multinational company subsidiary in Brazil illustrates how the model can be used to show the relative relevance of the different sources of cultural influences on key stages in organizational learning processes. The authors include the arts as an inherent dimension of culture that tends to be overlooked in the management literature, and the case illustrates how the arts can play a role in organizational learning for Global Responsibility.
Keywords: 330; corporate social responsibility; global responsibility; national and corporate culture; organizational learning; Brazil; youth unemployment